Synthesis of ribavirin 2’-Me-C-nucleoside analogues - Cosson, Fanny; Faroux, Aline; Baltaze, Jean-Pierre; Farjon, Jonathan; Guillot, Régis; Uziel, Jacques; Lubin-Germain, Nadège (Beilstein Journal of Organic Chemistry, 2017)
An efficient synthetic pathway leading to two carbonated analogues of ribavirin is described. The key-steps in the synthesis of these ribosyltriazoles bearing a quaternary carbon atom in the 2’-position are an indium-mediated alkynylation and a 1,3-dipolar cyclization.
Keywords: alkynylation; antiviral; cancer; C-nucleosides; ribavirin